Patient safety culture from the perspective of nursing technicians of an emergency sector - Micheline da Fonseca Silva; Manacés dos Santos Bezerril; Flávia Tavares Barreto Chiavone; Soraya Helena Medeiros de Morais; Maria Eduarda Gonçalves da Costa; Marianny Nayara Paiva Dantas; Viviane Euzébia Pereira Santos (Universidade Federal do Ceará, 2021)
Objective: to characterize the culture of patient safety from the perspective of nursing technicians of an emergency sector. Methods: cross-sectional study, developed in the emergency sector of a state hospital with 175 nursing technicians, from a 12-dimensional instrument on safety culture. The analysis of the data made based on the percentages of positive, negative and neutral responses of each dimension. Results: the culture of patient safety was characterized positively from the dimension Expectations about its supervisor/head and actions promoting patient safety (56.6%); negatively in the sphere Adequacy of professionals (75.5%); and in a neutral way, in the scope of Organizational Learning - continuous improvement (61.1%). Conclusion: it was understood that nursing technicians characterize the culture of patient safety in the emergency sector as an important aspect of the work environment, but that it needs to be optimized.